2020
DOI: 10.1051/0004-6361/201937164
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for hot corinos and WCCC sources in the OMC-2/3 filament

Abstract: Context. Solar-like protostars are known to be chemically rich, but it is not yet clear how much their chemical composition can vary and why. So far, two chemically distinct types of Solar-like protostars have been identified: hot corinos, which are enriched in interstellar Complex Organic Molecules (iCOMs), such as methanol (CH 3 OH) or dimethyl ether (CH 3 OCH 3 ), and Warm Carbon Chain Chemistry (WCCC) objects, which are enriched in carbon chain molecules, such as butadiynyl (C 4 H) or ethynyl radical (CCH)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 74 publications
4
26
0
Order By: Relevance
“…location of sources within the clouds and the ratio of CH 3 OH/C 2 H indicating the environmental effect on the chemistry. However, single-dish observations of CH 3 OH are contaminated by the contribution of the photodissociation region of the molecular clouds hosting the protostar (Bouvier et al 2020). In addition, chemical surveys with single-dish telescopes are often less sensitive to detect the COMs in the vicinity of the protostars.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…location of sources within the clouds and the ratio of CH 3 OH/C 2 H indicating the environmental effect on the chemistry. However, single-dish observations of CH 3 OH are contaminated by the contribution of the photodissociation region of the molecular clouds hosting the protostar (Bouvier et al 2020). In addition, chemical surveys with single-dish telescopes are often less sensitive to detect the COMs in the vicinity of the protostars.…”
Section: Notesmentioning
confidence: 99%
“…Single-dish surveys showed no correlation between COMs and long carbon-chain molecules (Graninger et al 2016;Higuchi et al 2018). Interestingly, carbon-chain molecules tend to distribute at a larger spatial scale than that of COMs (Imai et al 2016;Oya et al 2017;Bouvier et al 2020). Aikawa et al (2020) demonstrated that the conditions of prestellar cores can result in a larger spatial extent of carbon-chain molecules that coexist with COMs or deficient of carbon-chain molecules in COM-rich sources.…”
Section: Introductionmentioning
confidence: 99%
“…Two related questions arise: (1) Why are hot corinos so difficult to find? While it is known that not all Class 0/I sources possess hot corinos (e.g., Sakai & Yamamoto 2013;Higuchi et al 2018;Bouvier et al 2020), observational biases might hamper their detection. (2) Why do coeval objects seem drastically different in their chemical composition?…”
Section: Introductionmentioning
confidence: 99%
“…The Orion ALMA New Generation Survey (ORANGES) is a project aiming to study the molecular content, on small scales (≤1000 au), of the solar-type protostars located in the OMC-2/3 filament. It follows a large-scale (≤10 4 au) study of these same protostellar cores (Bouvier et al 2020). The focus of this previous study, carried out with the single-dish telescopes IRAM-30m 1 and Nobeyama-45m 2 , was to identify Warm Carbon Chain Chemistry (WCCC) protostars and hot corino candidates using observations of two species, CCH and CH 3 OH.…”
Section: Description Of the Projectmentioning
confidence: 99%
“…The ORANGES project consists of new ALMA observations at 246.2 GHz towards the same sample of sources studied in Bouvier et al (2020). The spatial resolution is about 0.…”
Section: Description Of the Projectmentioning
confidence: 99%